1787 N.C. Sess. Laws 813-14 - (:unkn) unknown (My University, 1787)
The militia law kept the militia as "all freemen and indented servants within this State, from eighteen to fifty years of age." The required arms and equipment were now more specific and varied by role in the militia. For commissioned officers in the infantry, "side arms" (handguns) "or a spontoon" (a pole arm). For private and non-commissioned officers, a musket or rifle, plus a cartridge box, powder horn, shot pouch "in good condition," "nine charges of powder made into cartridges with sizeable balls or swan-shot," a spare flint, and one worm and picker. As for artillerymen, they "shall be armed and accoutred with small arms in the same manner of the infantry, except the non-commissioned officers, who shall have swords instead of fire-arms." Horsemen, whether officers or privates, needed "a strong, serviceable horse, at least fourteen hands high, with a good saddle, bridle, holsters, one pistol, horseman's sword and cap, a pair of shoe boots and spurs," plus "a proper cartouch-box and cartridges all in good order."
Keywords: MILITIAS; REQUIRED POSSESSION